Administrative and Management Theory Development and its Application In Islamic Education - Suharto, Nugraha; Pribadi, Luthfi Audia (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This chapter provides an overview of several topics relevant to constructing an approach to teaching educational administration and leadership in Muslim countries. First, it places the topic in the context of the changing nature and critiques of the field that argue for a greater internationalization to both resist some of the negative aspects of globalization and to represent countries’ traditions in the professional curriculum. The study of education administration and management theory is a part that provides direction and views on how an educational administrator carries out his duties based on truth values, both practical and theoretical values. This journal will explain the theory of management and administration which is very important and influential in an institution. In its application, management and administration are a mutually sustainable unit so that an institution can achieve its goals if its leaders can manage the administration properly, be it the management of Human Resources, Finance, Infrastructure and so on. If the administrative arrangements can run well, then the management in an institution will automatically be organized by itself.